EFEKTIFITAS EKSTRAK DAUN KATUK (SAUROPUS ANDROGYNUS L.) DALAM MENGHAMBAT PERTUMBUHAN BAKTERI STAPHYLOCOCCUS AUREUS SECARA IN VITRO - Siti Fatimah; Yuliana Praetyaningsih; Aris Munandar (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Sauropus green (Sauropus adrogynus L.) is a plant that contains vitamins A, B, C, protein, fat,and minerals. Sauropus green leaf extract can also be used as an antibiotic that can inhibit thegrowth of gram-positive bacteria. Bacteria which can be inhibited by Sauropus green leafextract (Sauropus androgynus L.) is Staphylococcus aureus.This study used an experimentalresearch and diffusion method. The results obstained inhibition zones at concentrations 60%,80% and 100% with an average value of 8.3 mm, 9.6 mm and 12.6 mm. While at aconcentration of 20% to 40% showed no inhibition zone with an average value of 0.0 mm. Theresults of descriptive statistical tests through the program SPPS 17 of 15 concentration datagrowth inhibition zone diameter of Staphylococcus aureus bacteria standard deviation of 5.39.There is an effect on some Sauropus green leaf extract concentrations (Sauropus androgynus L.)inhibit the growth of Staphylococcus aureus at a concentration of 60%, 80% and 100% caninhibit the growth of Staphylococcus aureus. At concentrations of 20% and 40% no effectinhibiting the growth of Staphylococcus aureus bacteria. Keywords: diffusion method, sauropus green leaf extra